Sosialisasi Kebersihan Wisata di Sawakete Desa Afulu Kabupaten Nias Utara - Jeliswan Berkat Iman Jaya Gea; Nelman Waruwu; Franky Natalisman Lase; Hengky Pariaman Zalukhu; Erwin Jaya Gea; Irene Elvira Telaumbanua; Desitina Waruwu; Dedi Setianto Gea; Enisa Gea; Parman Lahagu; Otina Gea; Oktavianus Zega; Azlinda Halawa; Rasni Awaliyah Waruwu; Nyakdin Lahagu; Jefrin Putrawan Baeha; Wa'asaro Telaumbanua; Yamoguna Zalukhu; Ratna Elsofian Gul; Dalida Zisokhi Gea; Antonius Telaumbanua (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out at Sawa Kete Beach, Afulu Village, North Nias Regency, with the aim of raising collective awareness among the community about the importance of environmental cleanliness in the context of sustainable tourism management. The method used was descriptive-qualitative with a participatory approach, directly involving the community in socialization activities, installing information boards, distributing educational leaflets, and conducting joint community service activities. The results of the activity showed an increase in the community's understanding of the principles of waste management based on the 3R (Reduce, Reuse, Recycle) approach, as well as the emergence of a culture of maintaining cleanliness in the tourist area. Active participation from youth groups, housewives, and village officials serves as an indicator of the success of this collaborative approach. However, challenges such as inadequate waste management infrastructure and the absence of clear local regulations were also identified. Therefore, sustained collaboration between the village government, higher education institutions, and community groups is necessary to strengthen environmental management in tourist destinations. This program makes a tangible contribution to the development of clean, healthy, and competitive tourist villages through education, social action, and sustainable community empowerment.